EDUCATION FOR STEADY DEVELOPMENT: NEW ECOLOGICAL IMPERATIVE OF ECOPEDAGOGIKS - Lyubov V. Мazurina (Открытое образование (Москва), 2016)
A fundamental idea is presented is providing of steady development due to forming of the ecogeological world view based on understanding of harmonious existence of the system “Man and society are nature of planet Earth is Space”, revival of spiritual potential, acknowledged as a key condition of permission of ecological situation. Aimed at realization of the global passing to steady development by means of reengineering in the system of education, as a main tool of cognition of the World and increase of level of understanding of role of humanity.